2009
DOI: 10.1002/nbm.1369
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the human salivary metabolome

Abstract: Saliva is a readily accessible biofluid that is important for the overall health, aiding in the chewing, swallowing, and tasting of food as well as the regulation mouth flora. As a first step to determining and understanding the human saliva metabolome, we have measured salivary metabolite concentrations under a variety of conditions in a healthy population with reasonably good oral hygiene. Using (1)H NMR spectroscopy, metabolite concentrations were measured in resting (basal) and stimulated saliva from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(142 citation statements)
references
References 34 publications
4
125
4
2
Order By: Relevance
“…Most of the detected compounds identified in this study are consistent with those previously reported in the saliva of healthy individuals [23], [42][45]. Their possible entry routes into the salivary flow are very diverse and can include environmental exposure through the inhalation of air and/or water vapor ingestion, food intake, transdermal absorption, blood, oro-nasal tissues and gastrointestinal reflux.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the detected compounds identified in this study are consistent with those previously reported in the saliva of healthy individuals [23], [42][45]. Their possible entry routes into the salivary flow are very diverse and can include environmental exposure through the inhalation of air and/or water vapor ingestion, food intake, transdermal absorption, blood, oro-nasal tissues and gastrointestinal reflux.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, previous studies also have shown a direct relationship between the composition of parotid saliva and blood (4042). Parotid saliva has been shown to contain constituents of blood such as amino acids, pyruvate and lactate as revealed by a recent NMR study (43). We hypothesize that the high APT weighting in both the parotid gland and blood may be attributed to their similar underlying biochemical properties, but these metabolic sources should be further examined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, only approximately half of all saliva metabolites (88 compounds) were also detected in plasma. Although parotid saliva directly reflects the contents of blood (19), the overall content of metabolites in globally collected saliva also depends on other glands, most prominently the submandibular glands (20). Among the common metabolites detected, 27 were rhythmic in either plasma or saliva.…”
Section: Human Salivary Metabolome Also Shows Circadian Metabolismmentioning
confidence: 99%